Penerapan E-Learning sebagai Media Pembelajaran Berbasis Aplikasi Android Menggunakan Metode Research and Development - Jahiri, Muhamad; Diana Yusuf, Inayatul Izzati; M.Kom, Henderi; Henderi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The current development of information technology, especially the internet, can present virtual interaction spaces that are able to provide an unlimited number of sources or resources and can be accessed quickly anywhere and anytime. Currently, Indonesia is entering the era of the industrial revolution 4.0 which prioritizes technology in all fields including learning. But unfortunately the existence of learning media is still lacking, especially in vocational high schools, very few teachers use technology as learning media. E-learning is a type of teaching and learning that allows teaching materials to be conveyed to students using internet media, or other computer network media. E-learning needs to be used to familiarize students with technology. The research model on ADDIE was carried out with five main stages namely: analysis, design, development, implementation and evaluation. Data obtained by questionnaire. The data is then analyzed while the suggestions are used as the basis for revising the product. This study aims to: (1) Make E-learning using Flash Cs 6 at SMK Yanisba Boarding School (2) Determine the feasibility of E-learning using Flash Cs 6 at SMK Yanisba Boarding School. Evaluation of 4 validators on E-learning using Flash Cs 6.